ANALISIS KESULITAN BELAJAR TEKS ANEKDOT DENGAN STRATEGI GENIUS LEARNING - Iscan Ilham Nur Said; Reka Yudha Mahardika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The background this research is due to the low writing skills, especially the anecdotal text of class X students of SMA YKKP Bandung, seen from anecdotal essays that have not been able to create an impression for the reader. This study aims to analyze the difficulty writing skills in anecdotal texts in class X SMA YKKP Bandung in the academic year 2017/2018 by applying the learning genius strategyThe learning method applied is learning genius with experimental quasy design. The results obtained can be seen if the use of the genius learning strategy is more effective in the teaching and learning process of writing anecdotal texts. This difference is seen in terms of a more conducive learning atmosphere, students look more focused and students become more active because learning is more interesting. In addition, the work of students is further enhanced by the learning genius strategy. Overall the experimental class all aspects and criteria for writing anecdotes have improved compared to before the experiment. Based on the results of this study stated that the learning genius strategy can be an alternative to improve students' ability in writing anecdotal texts in class X students of SMA YKKP Bandung.